GENDER EQUALITY OF CHILDREN CARE RIGHTS FAZLUR RAHMAN'S HERMENEUTIC PERSPECTIVE - Darmawan, Darmawan; Musafa'ah, Suqiyah; Utami, Ria Cahyaning (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
This study aims to analyze gender equality in child custody rights (?a??nah) through Fazlur Rahman’s double movement hermeneutic framework. The research focuses on the relevance of Qur’anic and Prophetic texts regulating parental responsibilities, particularly QS Al-Baqarah: 233, QS At-Tahrim: 6, and several hadiths addressing custody arrangements. This study employs a qualitative library research design with a historical–contextual analytical approach. Through Rahman's hermeneutics, the research re-evaluates classical Islamic legal formulations that often prioritize mothers in custody decisions without considering contemporary social transformations. The findings reveal that sociocultural contexts and patriarchal structures of early Muslim societies significantly influenced classical custody rulings. Therefore, modern custody decisions should emphasize child welfare, parental capability, psychological stability, and shared responsibility rather than gender-based assumptions. The study concludes that Islam fundamentally offers equal opportunities for both parents to assume childcare responsibilities. Accordingly, custody arrangements must prioritize the child's best interests and align with the moral principles of justice, compassion, and cooperation embedded in Islamic teachings. This hermeneutic reinterpretation highlights the necessity of contextual legal reasoning to ensure gender-balanced and child-centered custody practices.